2012
DOI: 10.3109/03009742.2012.700487
|View full text |Cite
|
Sign up to set email alerts
|

CCL5/RANTES in ANCA-associated small vessel vasculitis

Abstract: No abstract availabl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…IP10 is a strong attractant for macrophages and NK cells. RANTES is responsible for the recruitment of T cells, dendritic cells, eosinophils, NK cells, and monocytes to sites of inflammation [42,43]. Two previous studies have shown elevated levels of RANTES in acute IgAV, and one of them has also shown its increase in patients with internal organ involvement compared to patients without organ involvement [15,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IP10 is a strong attractant for macrophages and NK cells. RANTES is responsible for the recruitment of T cells, dendritic cells, eosinophils, NK cells, and monocytes to sites of inflammation [42,43]. Two previous studies have shown elevated levels of RANTES in acute IgAV, and one of them has also shown its increase in patients with internal organ involvement compared to patients without organ involvement [15,44].…”
Section: Discussionmentioning
confidence: 99%
“…Our study did not show significant differences in RANTES and IP10 concentration between the groups studied. However, it was shown that chemokines play a role in many inflammatory diseases such as systemic lupus erythematosus, Kawasaki disease, Wegener’s granulomatosis, and Behcet’s disease [ 40 42 ]. IP10 is a strong attractant for macrophages and NK cells.…”
Section: Discussionmentioning
confidence: 99%